Communicating with the Spirits - Pócs, Éva; Klaniczay, Gábor (Demons, spirits, witches ;, 2005)
Focuses on the problem of communication with the other world: the phenomenon of spirit possession and its changing historical interpretations, the imaginary schemes elaborated for giving accounts of the journeys to the other world and for communicating with the dead, and finally the historical archetypes of this kind of religious manifestation -- trance prophecy, divination, and shamanism.